Frequency of prion genotypes in Cikta sheep - Kovács, Endre; Tempfli, Károly; Zenke, Petra; Maróti-Agóts, Ákos; Sáfár, László; Gáspárdy, András (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
The authors study the current status of Hungarian Cikta Sheep based on genetic background of scrapie resistance. The aim of this investigation was to estimate the relative frequency of prion haplotypes, -genotypes, and risk categories as well as to reveal the efficiency of scrapie eradication program achieved over the last decade. The authors confirmed based on larger sample size the previous knowledge, that the resistance against scrapie of Cikta breed is considered as low, and the classification of this breed according to risk category has not been improved. However, the frequent haplotype ARQ and risk category 3 can also be considered for breed specificity. The careful breeding of them is permitted and will contribute to the maintenance of breed diversity according to other aspects.